2015
DOI: 10.1242/dmm.017723
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal diabetes on the Wnt/PCP pathway during embryogenesis as reflected in the developing mouse eye

Abstract: Embryopathies that develop as a consequence of maternal diabetes have been studied intensely in both experimental and clinical scenarios. Accordingly, hyperglycaemia has been shown to downregulate the expression of elements in the non-canonical Wnt-PCP pathway, such as the Dishevelled-associated activator of morphogenesis 1 (Daam1) and Vangl2. Daam1 is a formin that is essential for actin polymerization and for cytoskeletal reorganization, and it is expressed strongly in certain organs during mouse development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
2
12
0
Order By: Relevance
“…The three genotypes had a clear impact on the final phenotype (for both Mthfr and Folr1 ), demonstrating the potential risk of maternal diabetes and any other environmental factor that alters gene expression, relevant to embryonic development. Indeed, maternal diabetes appears to be capable of making an embryonic recessive mutation behave like a dominant mutation, or of increasing the incidence of a rare phenotype, as observed previously . Here, the incidence of embryos with NTDs increased with the reduction in embryonic Mthfr dosage and therefore activity (see, in a maternal hyperglycemic background.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The three genotypes had a clear impact on the final phenotype (for both Mthfr and Folr1 ), demonstrating the potential risk of maternal diabetes and any other environmental factor that alters gene expression, relevant to embryonic development. Indeed, maternal diabetes appears to be capable of making an embryonic recessive mutation behave like a dominant mutation, or of increasing the incidence of a rare phenotype, as observed previously . Here, the incidence of embryos with NTDs increased with the reduction in embryonic Mthfr dosage and therefore activity (see, in a maternal hyperglycemic background.…”
Section: Discussionsupporting
confidence: 61%
“…As such, we exposed embryos to hyperhomocysteinemic conditions to recapitulate the homocysteine accumulation that can occur during folate deficiency. Embryos were divided into four equivalent groups depending on the treatment received, and after 18 hours in culture, the embryos were evaluated for gross external malformations: controls (n = 42), embryos exposed to PBS alone; homocysteine embryos (n = 30) exposed to 0.5 mM homocysteine (based on Reference ; glucose embryos (n = 39), exposed to 20 mM glucose (based on Reference ; and glucose and homocysteine embryos (n = 46), exposed to 20 mM glucose and 0.5 mM homocysteine (data summarized in Table ). Those embryos with less than 16 somites before culture that reached >19 somites after culture were evaluated for cranial closure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, peaks associated with the genes in the BMP, FoxP1, and Wnt cardiac morphogenetic signaling pathways were identified, and they have been linked to increased risk of fetal neurologic and cardiac developmental defects in matDM-exposed embryos (61)(62)(63)(64)(65). HG stress resulted in dysregulation of chromatin accessibility of genes important for reorganizing actin cytoskeleton, cell polarity, and alignment during tissue morphogenesis (66,67). Interestingly, our data demonstrated that peaks associated with genes involved in chromatin regulation were also altered in the setting of HG (Supplemental Figure 8, A-C, and Supplemental Table 17).…”
Section: Discussionmentioning
confidence: 99%